PENYUSUNAN RENCANA TATA RUANG DESA (RTRWDES) SECARA PARTISIPATIF DI DESA MUARA SIRAN DAN DESA LIANG BUAYA KECAMATAN MUARA KAMAN KABUPATEN KUTAI KARTANEGARA - Saparwadi Saparwadi; Yohanes Budi Sulistioadi; Rujehan Rujehan (Fakultas Kehutanan Universitas Mulawarman, 2020)
This study aims to obtain information on plans and spatial use patterns and spatial structures in Muara Siran and Liang Buaya villages and compile information on land cover and socio-economic conditions of the community. Muara Siran Village Spatial Plan and Liang Buaya Village Spatial Plan are divided into 2 areas, namely the Cultivation Zone and the Protected Area. The preparation of the RTRW of Muara Siran Village and Liang Buaya Village is the first example for the Regency Government in the preparation of a participatory Village RTRW in the Kutai Kartanegara District environment. The people of Muara Siran Village and Liang Buaya Village are dominated by the Kutai tribe, most of whose livelihoods are fishing, farming and cage cultivation. So that village spatial planning becomes very important in the utilization and control of natural resources. With the implementation of the participatory village spatial planning concept, it needs to be replicated by other villages in Kutai Kartanegara Regency to support development as well as to protect the area through spatial planning so that in future development planning is in accordance with the potential of each village.